A Preliminary Study of a Lettuce-Based Edible Vaccine Expressing the Cysteine Proteinase of Fasciola hepatica for Fasciolosis Control in Livestock - Wesołowska, Agnieszka; Kozak Ljunggren, Monika; Jedlina, Luiza; Basałaj, Katarzyna; Legocki, Andrzej; Wedrychowicz, Halina; Kesik-Brodacka, Małgorzata (Frontiers in Immunology, 2018)
Oral vaccination with edible vaccines is one of the most promising approaches in modern vaccinology. Edible vaccines are an alternative to conventional vaccines, which are typically delivered by injection. Here, freeze-dried transgenic lettuce expressing the cysteine proteinase of the trematode Fasciola hepatica (CPFhW) was used to orally vaccinate cattle and sheep against fasciolosis, which is the most important trematode disease due to the parasite’s global distribution, wide spectrum of host species and significant economic losses of farmers. In the study, goals such as reducing the intensity of infection, liver damage and F. hepatica fecundity were achieved. Moreover, we demonstrated that the host sex influenced the outcome of infection following vaccination, with female calves and male lambs showing better protection than their counterparts. Since differences occurred following vaccination and infection, different immunization strategies should be considered for different sexes and host species when developing new control methods. The results of the present study highlight the potential of oral vaccination with plant-made and plant-delivered vaccines for F. hepatica infection control.